Impact of resolution on the atmosphere–ocean coupling along the Gulf Stream in global high resolution models - E. E. Tsartsali; R. J. Haarsma; P. J. Athanasiadis; A. Bellucci; H. de Vries; S. Drijfhout; I. E. de Vries; D. Putrahasan; M. J. Roberts; E. Sanchez–Gomez; C. D. Roberts (Climate Dynamics, 2022)
We have investigated the horizontal resolution dependence of the ocean–atmosphere coupling along the Gulf Stream, of simulations made by six Global Climate Models according to the HighResMIP protocol, and compared it with reanalysis and remote sensing observations. Two ocean–atmosphere interaction mechanisms are explored in detail: The Vertical Mixing Mechanism (VMM) associated with the intensification of downward momentum transfer, and the Pressure Adjustment Mechanism (PAM) associated with secondary circulations driven by pressure gradients. Both VMM and PAM are found to be active even in the eddy-parameterized models. However, increasing ocean and/or atmosphere resolution leads to enhanced ocean–atmosphere coupling and improved agreement with reanalysis and observations. Our results indicate that while one part of the stronger air–sea coupling is attributable to the refinement of the oceanic component to eddy-permitting, optimal results are obtained only by further increase of the atmosphere resolution too. The use of the eddy-resolving model show weaker or same coupling strength over the eddy-permitting resolution. We conclude that at least eddy-permiting ocean resolution and comparable atmosphere resolution are required for a reliable ocean–atmosphere coupling along the Gulf Stream.